Quasi-Materials and the Making of Interior Atmospheres - Sadar, John Stanislav (UI Scholars Hub, 2018)
In The Architecture of the Well-Tempered Environment, Reyner Banham presents a parable in which, having come across an amount of wood, a nomadic tribe must decide how to use it to keep warm overnight: build a structure or build a fire (and burn the wood as fuel). The first of these uses the materials directly to create an amenable interior condition using the tangible materiality of geometric construction. The second, however, generates heat from combustion, thereby creating an intangible, graduated, thermal interiority, which one can draw deeper into, by moving closer to the fire, or recede from, by moving away. Interior architecture has largely been concerned with achieving shelter and creating an interior atmosphere through the dependability and predictability of physical materials. Less often has interior architecture considered the interiority achieved through the temporal contingency of atmospheric quasi-materials (taking a cue from Tonino Griffero’s quasithings), phenomena such as light, sound, temperature, and humidity. While these often strike one as outside of the realm of designers, their effects profoundly colour our experiences of our environments: the smells of street food, the heat of the metro air exhaust, the veil of fog rolling in. A selection of student projects probing quasi-materials in interior architecture reveals their nature and potential for making interior environments. More akin to building a fire than fitting out a shell, these projects question existing tenets of interior architecture, while they enable types of interiority that are fluid, graduated and temporal.